2022
DOI: 10.3346/jkms.2022.37.e94
|View full text |Cite
|
Sign up to set email alerts
|

Hearing and Speech Perception for People With Hearing Loss Using Personal Sound Amplification Products

Abstract: Background Hearing loss (HL) is the most common chronic disease and has been linked to negative health outcomes. Hearing aids (HAs) are regarded as the gold standard for HL management, however, the adoption rate of HAs is relatively low for various reasons. With this background, hearing devices, such as personal sound amplification products (PSAPs) received significant attention as an alternative to conventional HAs. This study aimed to evaluate the clinical efficacy of PSAPs in patients with mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
3
10
0
Order By: Relevance
“…Specifically, participants were more accurate in discriminating words in noise and repeating sentences under high noise levels in the QuickSIN test with the PSAPs. This is consistent with previous studies showing that PSAPs are associated with better listening ability than an unaided condition [ 21 , 22 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Specifically, participants were more accurate in discriminating words in noise and repeating sentences under high noise levels in the QuickSIN test with the PSAPs. This is consistent with previous studies showing that PSAPs are associated with better listening ability than an unaided condition [ 21 , 22 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…Another factor that could explain the gain in speech-in-noise perception is that the PSAPs currently on the market might not be effective enough to provide clinically relevant benefits, as they do not all have the same features as conventional hearing aids. This would be consistent with a previous study that examined the impact of five different PSAPs and hearing aids on listening ability [ 21 ]. Their results showed that all PSAPs improved auditory processing, but the gains were significantly less than conventional hearing aids.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations